RESEARCH OF MODERN STEGANOGRAPHIC METHODS AND MEANS FOR PROCESSING DIGITAL IMAGES - Юдін, О. К.; Симониченко, Я. А.; Симониченко, А. А. (Science-based technologies, 2017)
The article deals with the study of modern steganographic methods and tools for processing digital images using software tools that are freely available through the Internet and available to the ordinary citizen. During the study, was performed identify the structural changes in graphics files which are the results, as well as, the result's images and the original's images. Was performed such comparisons: changes the size of graphics files; counting the number of modified pixel values of the images; study of the modification of the color image components and their respective bit planes; comparison of the structure of the received files. On the basis of the conducted researches were the results of relatively modern implementation methods hide information by steganography software that can be used in the future to improve the efficiency of steganographic system or steganographic analysis.